Discovering jazz [videorecording] - Wilets, Bernard (Chicago Encyclopedia Britannica Educational Corporation [producer], 1990)
Traces the origin of jazz as an American art form.
VHS.
Advisor, Paul Taner.
Keywords: Jazz; Jazz musicians; Jazz -- United States